Plasma IL‐12/IFN‐γ axis predicts cognitive trajectories in cognitively normal older adults: Biomarkers (non‐neuroimaging)/Plasma/Serum/Urine biomarkers. (7th December 2020) - Yang, Hyun‐Sik; Zhang, Can; Carlyle, Becky C.; Zhen, Sherri Y; Trombetta, Bianca A.; Schultz, Aaron P.; Pruzin, Jeremy J.; Fitzpatrick, Colleen D.; Kirn, Dylan; Rentz, Dorene M.; Arnold, Steven E.; Johnson, Keith A.; et al.
Abstract: Background: The immune system plays a critical role in Alzheimer's disease (AD) pathophysiology, and altered peripheral cytokine levels have been reported in AD dementia. However, it remains unclear whether and how plasma cytokines in cognitively normal (CN) older adults predict cognitive decline. Method: We studied 298 CN Harvard Aging Brain Study (HABS) participants with baseline amyloid‐β (Aβ) measure (Pittsburgh Compound B PET neocortical distribution volume ratio (DVR)), baseline plasma collection, and longitudinal cognitive measures (Preclinical Alzheimer Cognitive Composite 5 (PACC5)). We measured nine plasma cytokines (IFN‐γ, IL‐1b, IL‐4, IL‐6, IL‐8, IL‐10, IL‐12p70, IL‐13, TNF‐α) using the Meso‐Scale Discovery V‐PLEX platform, and the cytokine levels were log‐transformed and normalized. We first screened for the cytokines that modify the association between baseline Aβ and longitudinal PACC5 (linear mixed effect models). We then screened the remaining cytokines for their Aβ‐independent association with longitudinal PACC5 (linear mixed effect models). The identified cytokines' association with Aβ ("A"), neocortical tau ("T") (inferior temporal cortex flortaucipir PET standardized uptake value ratio (SUVR) at Year 4), and neurodegeneration (longitudinal hippocampal volume (HV)) ("N") were tested. Result: Higher baseline plasma IL‐12p70 modified the association between baseline Aβ and longitudinal cognition, whereby higher IL‐12p70 predicted less cognitive decline especially in the setting of higher Aβ (IL‐12p70*Aβ*time: β=0.17, p=3.6×10 ‐5, FDR=3.2×10 ‐4 ): higher IL‐12p70 predicted less cognitive decline in the Aβ+ subgroup (n=72; β=0.085, p=4.0×10 ‐4 ), but not in the Aβ‐ subgroup (n=221; p=0.33). IL‐12p70 was not associated with baseline Ab (p=0.79), but its interaction term with baseline Ab predicted lower neocortical tau burden at Year 4 (n=118; β=‐0.15, p=0.040), and less longitudinal hippocampal volume loss (n=244; β=42, p=0.035). On the other hand, higher IFN‐γ was associated with less cognitive decline independent of Aβ (IFN‐γ*time: β=0.026, p=1.5×10 ‐3, FDR=0.011). IFN‐γ was not associated with Aβ, tau, or longitudinal hippocampal volume. Conclusion: Plasma IL‐12/IFN‐γ axis predicted a favorable cognitive trajectory in CN older adults, and plasma IL‐12p70 captured a process that modifies the association of Aβ with neocortical tau and longitudinal neurodegeneration. Our results showing protective effect of upregulated peripheral IL‐12/IFN‐γ axis illustrate complex roles the immune system plays in the progression of AD.